From Uncertain Space: Spatial Trajectory of a Social Innovation ‘by Withdrawal’. Study of the Composition of the Association of Lodges and Huts in Queyras (Hautes-Alpes, France) - Yann Borgnet (Revue de Géographie Alpine)
Alpine territories located outside major ski areas have often developed in contrasting ways: On the one hand, improvements are made for alpine skiing; on the other hand, there is a need to build an alternative model that supports other practices and other seasons besides winter. Queyras has followed this cyclical process by alternating between good periods of development driven by innovation and periods of crisis. This paper traces the growth of a host association that has been promoting wayfaring activities for the past 15 years. This association has become an important player in promoting these activities and is identified by tourism stakeholders as a major tool to leverage the future of Queyras’s identity as a tourist destination. The association’s developmental trajectory is regularly affected by the withdrawal of non-human actors. While they had previously structured and balanced its support network, the latter has had to be (re)configured around new actors and actants. Our conclusions suggest there is an improvised evolution towards agility and freedom of action as the institutional actor gradually retreats. Recently, this evolution has been accompanied by various translation processes aimed at restoring overall coherence through a superior common territorial principle associated with civic and ecological cities.